Impact of external sector developments on Caribbean economic performance 1983-1988. - Harker, Trevor (1991)
Explains how many of the problems present during the initial years of the 80s continued to have important effects on Caribbean economies. Examines the external sector in the context of international economic developments, the changes in the main markets for Caribbean goods and services, and regional economic performance.